Pengaruh budaya organisasi dan kompensasi terhadap kinerja karyawan PT Eka Dura Indonesia Rokan Hulu - Indah Zilarsy; Sri Indarti; Iwan Nauli Daulay (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research aim to know how influence Organizational Culture variable and Compensation by simultan and partial to the Employees performance at PT Eka Dura Indonesia Rokan Hulu. In this research there are 135 sample from the total employees at PT Eka Dura Indonesia Rokan Hulu. The used analyze in this research is descriptive analyze, and then also used quantitative analyze with the make by SPSS program version 18. From the result examination double linear regresion analyze, which have been simultan test (test F) indicated that Organizational Culture and Compensation variable have been significant effect to the employees performance. Result of partial test (test T), indicating that Organizational Culture variable more dominant have a significant effect to the employees performance. And the Compensation variable also have a significant effect to the emloyees performance at PT Eka Dura Indonesia Rokan Hulu.Keywords: Organizational Culture, Compensation and Employees Performance.